Β‐arrestin‐1 mediates the TCR‐triggered re‐routing of distal receptors to the immunological synapse by a PKC‐mediated mechanism. (6th February 2014) - Fernández‐Arenas, Elena; Calleja, Enrique; Martínez‐Martín, Nadia; Gharbi, Severine I; Navajas, Rosana; García‐Medel, Noel; Penela, Petronila; Alcamí, Antonio; Mayor, Federico; Albar, Juan P; Alarcón, Balbino
Synopsis <boxed-text content-type="graphic" id="embj201386022-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Activated T‐cell receptors (TCRs) employ β‐arrestin‐mediated internalization to downregulate migratory chemokine receptors, but surprisingly also to recruit unliganded peripheral TCRs to the immunological synapse. β‐arrestin‐1 binds non‐phosphorylated tyrosine containing motifs, ITAMs, of the TCR. TCR triggering stimulates the phosphorylation by PKC of Ser163 in the phosphate sensor sequence of β‐arrestin‐1. Ser163 phosphorylation is required for β‐arrestin‐1 recruitment to the TCR. β‐arrestin‐1 is required for the TCR triggered downregulation of bystander TCRs and CXCR4. β‐arrestin‐1‐mediated downregulation of distal TCRs allows the immunological synapse to be fed with new TCRs and to sustain the TCR signal.